Serous Macular Detachment Secondary to Optic Pit: Surgical Treatment and Long Time Results - Selim Cevher; Nedime Sahinoglu-Keskek; Fikret Unal; Selahaddin Demirduzen; Huseyin Oksuz (Case Reports in Ophthalmological Medicine)
32-year-old Turkish male patient presented with an optic disk pit and serous macular detachment in the left eye. Spectral domain optical coherence tomography revealed serous macular detachment and retinoschisis. After vitrectomy the retina gradually flattened and vision was gradually improved. We aimed to report a case of serous macula detachment secondary to optic pit and long term result of surgical treatment.